Lifestyle of Elderly People With Osteoporosis and Its Related Factors - Esmaeil Fallah Mehrabadi; Minoo Pakgohar; Sedigheh Asadi; Hamid Haghani (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Given the aging process of the population and the important role of lifestyle in common and chronic diseases, especially osteoporosis in the elderly, this study was conducted to evaluate the lifestyle of elderly people with osteoporosis. Methods & Materials This cross sectional (descriptive-analytic) study was carried out in 2013 on 300 osteoporotic elderly people who were referred to the bone densitometry centers of Tehran University of Medical Sciences, Tehran, Iran. Convenience sampling method was used, and the data were collected using a questionnaire for measuring healthy lifestyle in Iranian elderly. The collected data were analyzed by descriptive statistics including ANOVA and t-test by using SPSS-PC (V. 21) and P≤0.05. Results Results showed that the lifestyle of most osteoporotic elderly people (71.3%) was moderate, 10.7% of them had a desirable lifestyle, and 18% had an undesirable lifestyle. There was no statistically significant difference between the overall average score of lifestyle with age (P=0.499) and sex (P=0.176) in older adults with osteoporosis, but significant difference was statistically observed between the overall average score of lifestyle and marital status (P=0.001), educational level (P=0.027), and chronic disease (P=0.009). Conclusion Due to the increasing elderly population and the prevalence of osteoporosis in them, it is recommended that health officials and policy makers in the country should pay more attention in this area to prevent the occurrence of the disease as well as improve the lifestyle of elderly people with osteoporosis.